(untitled) (Journal of the Management Sciences, 2024)
The study examines factors affecting Women entrepreneurial and Household Wellbeing in Biu, LGA Borno State, Nigeria. A qualitative and quantitative approach is adopted to conduct the research study. A primary and secondary source of data gathering was used. The study population consist about 1242 small-scale entrepreneurs. Due to dearth of financial capability, the study made use of Taro Yamane’s formula to determined the sample size and approximately 400 participants are selected with the aid of simple random sampling technique and structured questionnaires were administered to the respondents. Simple percentages, were used to tabulate the results while chi-square was used to test the hypotheses. Social network theory was used to backed the study. The results showed that factors such as low electricity supply, infrastructural decay, corruption, inadequate skills, inadequate credit facilities, and security challenge must be addressed quickly in order to create enabling environment for business enterprises generally. The study further established that the aforementioned findings, consequentially have dreadful implication for growth and development in Nigeria. Therefore, the study greatly emphasized as its major recommendation, the need for the government and its agencies to deploy more commitment in order to sustain policies that will advance the headway of women entrepreneurship and Household Wellbeing in Nigeria. To a large extent, it will spur the nation toward achieving SDGs (agenda 9) which, Nigeria is a signatory among comity of the world.